Nanoparticle-Delivered HIV Peptides to Dendritic Cells a Promising Approach to Generate a Therapeutic Vaccine - Alba Martín-Moreno; José L. Jiménez Blanco; Jamie Mosher; Douglas R. Swanson; José M. García Fernández; Ajit Sharma; Valentín Ceña; María Angeles Muñoz-Fernández (MDPI AG, 2020)
Finding a functional cure for HIV-1 infection will markedly decrease the social and economic burden of this disease. In this work, we have taken advantage of the antigen presenting cell role of human dendritic cells (DCs) to try to induce an immune response to HIV-derived peptide delivered to DCs using two different polycationic nanoparticles: a G4 PAMAM dendrimer modified to a 70/30 ratio of hydroxyl groups/amines and a cyclodextrin derivative. We have studied peptide delivery using a fluorescence peptide and have studied the immune response generation by cytokine determination and flow cytometry. We have found a robust delivery of the antigenic peptide to DCs and activated dendritic cell-mediated peripheral blood mononuclear cells (PBMCs) proliferation using the mixed lymphocyte reaction. However, no expression of markers indicating activation of either B or T lymphocytes was observed. Moreover, the release of the pro-inflammatory cytokine TNF-α or IL-2 was only observed when DCs treated with either the dendrimer or the dendriplex containing the peptide. Antigenic peptide delivery to DCs is a promising approach to generate a vaccine against HIV-1 infection. However, more studies, including the simultaneous delivery of several antigenic peptides from different viral proteins, can markedly improve the immune response.